Answer:
x = -3
y = -3
Explanation:
To solve this system of equations, you can use the elimination method, which is to have one of the variables match, but be the opposite sign of the other:
- x + y = 0
4x - 3y = -3
The easier one to match is the 1st equation, and to make it match oppositely, you multiply the whole equation by 4:
4(-x + y = 0)
-4x + 4y = 0
4x - 3y = -3
-4x and 4x cancel each other out:
4y = 0
-3y = -3
_______
y = -3
Then plug in -3 for y, into one of the equations:
- x + y = 0
- x - 3 = 0
Add 3 to both sides:
- x = 3
Divide both sides by -1:
x = -3